Shallow Tectonic Stress Magnitudes at the Hikurangi Subduction Margin, New Zealand - E. Behboudi; D. D. McNamara; I. Lokmer (Geochemistry, Geophysics, Geosystems, 2023)
Abstract Quantifying tectonic stress magnitudes is crucial in understanding crustal deformation processes, fault geomechanics, and variable plate interface slip behaviors in subduction zones. The Hikurangi Subduction Margin (HSM), New Zealand, is characterized by along‐strike variation in interface slip behavior, which may be linked to tectonic stress variations within the overriding plate. This study constrains in situ stress magnitudes of the shallow (<3 km) overriding plate of the HSM to better understand its tectonics and how they relate to larger scale subduction dynamics. Results reveal σ3: Sv ratios of 0.6–1 at depths above 650–700 m TVD and 0.92–1 below this depth interval along the entire HSM. Additionally, for depths below 650–700 m TVD, SHmax: Sv ratios of 0.95–1.81 in the central HSM and 0.95–2.3 in the southern HSM are estimated. These stress ratios suggest a prevalent thrust to strike‐slip (σ1 = SHmax) faulting regime across the central and southern HSM. In the central HSM, the presence of NNE‐NE striking reverse faults co‐existing with a modern σ1 (SHmax) aligned ENE‐WSW suggests that overtime the stress state here evolved from a contractional to a strike‐slip state, where the compressional direction changes from perpendicular (NW‐SE) to oblique (ENE‐WSW) to the Hikurangi margin. This temporal change in stress state may be explained by forearc rotation, likely combined with the development of upper plate overpressures. In the southern HSM, the modern WNW‐ESE/NW‐SE σ1 (SHmax) and pre‐existing NNE‐NE striking reverse faults indicate that stress state remains contractional and perpendicular (NW‐SE) to the Hikurangi margin overtime.